Dendrimers: Patents for Alzheimer’s Disease - Maheshwari, Shubhrat; Singh, Aditya (Recent Patents on Nanotechnology, 2025)
Cells and nervous system connections that are crucial for movement, coordination, strength, sensation, and thought are gradually damaged in neurodegenerative illnesses. Amyloid beta (Aβ)-accumulating macromolecules in the brain are the primary cause of the disease's chronic symptoms, according to analysis carried out during the last 20 years. Plaques and clumps of amyloid- build up in the brain, obstructing neuronal signals and destroying neural connections. Tau, a protein that results in the formation of “neurofibrillary tangles” in the brain, another hallmark of neuronal death, has been the focus of a lot of research. Dendrimers Delivery (DDs) is one of the most promising advancements in nanotechnology for biomedical applications, particularly drug delivery. Some of the main categories of dendrimers employed in the successful management of neurodegenerative illnesses are polyamidoamine dendrimers (PAMAM) dendrimers, polypropylenimine dendrimers (PPI), Poly-l-lysine dendrimers (PLL), and carbosilane dendrimers. The tight blood-brain barrier (BBB), which limits the entry of medications or therapeutic agents, makes it difficult to treat central nervous system disorders. Dendrimers have attracted the attention of scientists more than other non-invasive methods of drug delivery across the BBB and improve the uptake of medicines in the brain's target tissues. The major benefits of dendrimers include their adaptability, biocompatibility, ability to load pharmaceuticals into the core and surface, and nanosize. The patents provide “composition of matter” protection for Starpharma's dendrimer technologies for drug delivery out to 2029 in the United States, which is the world's largest pharmaceutical market for several important drug classes. This review has updated the status of the patent and clinical trials literature pertaining to dendrimer use in AD.
Keywords: blood-brain barrier